PROSPECTS FOR CHANGES IN THE ORGANIZATION OF BANKS IN THE LIGHT OF THE CONCEPT OF PAYMENT SERVICES HUB - Iwańczuk-Kaliska, Anna (Acta Universitatis Lodziensis. Folia Oeconomica, 2014)
Contemporary banks face a number of challenges arising from development of financial markets, globalization and technological and communication revolution. These challenges comprise significant and multifaceted changes in the market for payment services, which affect the functioning of commercial banks, including indirectly their organization.The aim of this study is to assess the potential impact of the idea of payment services hub on changes in the organization of the banking business. To achieve this objective, the different forms of centralization and integration of the infrastructure and processes in the area of payment services were presented. Next, the reference to the consequences of the concept of payment services hub for the organization of banks was made. The hypothesis of this article is as follows: full centralization of intra-bank systems, processes and activities related to the execution of payment services, will lead to the organisational division of business of some banks to the deposit-credit institution and the payment institution.The findings formulated in the article point to the need to consider in the banks’ strategies their role in a national, European and global payments market. They also show the need for a review of the organization of the banks’ operation, taking into consideration the concept of full centralization of payment services and integration of internal processes associated with their implementation. These changes may result in full separation of business as service providers from the organizational structure of banks, especially under European regulations.